Genetic and combinatorial algorithms for optimal sizing and placement of active power filters - Maciążek, Marcin; Grabowski, Dariusz; Pasko, Marian (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with cost effective compensator placement and sizing. It becomes one of the most important problems in contemporary electrical networks, in which voltage and current waveform distortions increase Lear-by-year reaching or even exceeding limit values. The suppression of distortions could be carried out by means of three types of compensators, i.e., passive filters, active power filters and hybrid filters.
Keywords: power quality; optimization; active power filters; harmonics; genetic algorithms; combinatorial algorithms